"It's Not Easy, But It Needs to Be Done": Educators' Perceptions of Preparedness to Teach Students With Internalizing Mental Health Needs. (May 2023) - Firestone, Allison R.; Cruz, Rebecca A.
This mixed methods study surveyed 209 K-12 special education teachers about their perceptions of preparedness to teach students with mental health needs that manifest internally (e.g., quiet distress, withdrawal, excessive worry). We used a construct-modeling approach to develop the survey instrument and establish evidence of validity, reliability, and fairness, and it included both multiple-choice questions, used for descriptive and regression analyses, and open-ended items, coded to identify key themes. Results indicated that special educators generally had low perceptions of preparedness to support students with internalizing needs. In addition, we found that participants possessed critical misconceptions about research-based practices for supporting students with these needs in the school context, and that differences in perceptions of preparedness were associated with teachers' race and the grade level at which they taught.